Comparison of experimental and theoretical quantum-state-selected integral cross-sections for the H2O+ + H2 (D2) reactions in the collision energy range of 0.04–10.00 eV. Issue 32 (28th July 2016) - Song, Hongwei; Li, Anyang; Guo, Hua; Xu, Yuntao; Xiong, Bo; Chang, Yih-Chung; Ng, C. Y.
Abstract : A combined experimental–theoretical study of the rovibrationally state-selected ion–molecule reactions H2 O + (X 2 B1 ; v 1 + v 2 + v 3 + ; N Ka + Kc + + ) + H2 (D2 ) → H3 O + (H2 DO + ) + H (D), where ( v 1 + v 2 + v 3 + ) = (000), (020), and (100) and N Ka + Kc + + = 000, 111, and 211 . Abstract : To understand the dynamics of H3 O + formation, we report a combined experimental–theoretical study of the rovibrationally state-selected ion–molecule reactions H2 O + (X 2 B1 ; v 1 + v 2 + v 3 + ; N Ka + Kc + + ) + H2 (D2 ) → H3 O + (H2 DO + ) + H (D), where ( v 1 + v 2 + v 3 + ) = (000), (020), and (100) and N Ka + Kc + + = 000, 111, and 211 . Both quantum dynamics and quasi-classical trajectory calculations were carried out on an accurate full-dimensional ab initio global potential energy surface, which involves nine degrees of freedom. The theoretical results are in good agreement with experimental measurements of the initial state specific integral cross-sections for the formation of H3 O + (H2 DO + ) and thus provide valuable insights into the surprising rotational enhancement and vibrational inhibition effects in these prototypical ion–molecule reactions that play a key role in the interstellar generation of OH and H2 O species.